Preserving ecological balance through forest management, the sasami tradition, and sustainable food adaptation - Fadhil, Fathan Ahmad; Surtikanti, Hertien Koosbandiah (Journal of Critical Ecology, 2025)
Background: Amidst the pressures of modernization, the local wisdom of indigenous communities offers a relevant model for sustainability. This study deeply examines the integrated socio-ecological system in the Cireundeu Indigenous Village, which has successfully maintained ecological balance through ancestral traditions. Methods: Using a qualitative case study approach, data were collected through literature review, in-depth interviews with a customary leader, and participatory observation. Findings: The results indicate that the resilience of the Cireundeu system is supported by three interconnected pillars: (1) a customary forest zoning system (leuweung larangan, tutupan, baladahan) as a functional conservation practice; food adaptation based on cassava (Rasi) as a foundation for food sovereignty; and a mechanism for transmitting Traditional Ecological Knowledge (TEK) through the Surasa dialogue forum and customary rituals. Conclusion: The analysis concludes that these pillars are not separate practices but are holistically interconnected within a socio-ecological system. The sustainability of this system is underpinned by a web of positive feedback loops between spiritual beliefs, social institutions, and tangible ecological outcomes, offering a potent counter-narrative to fragmented modern development paradigms. Novelty/Originality of this article: The novelty of this article lies in its holistic analysis of how interconnected socio-ecological practices in Cireundeu Indigenous Village—spanning forest zoning, cassava-based food sovereignty, and knowledge transmission through rituals—form a sustainable resilience model that counters fragmented modern development paradigms.